Adiabatic RF pulse design for Bloch‐Siegert B+ mapping. Issue 3 (5th October 2012) - Khalighi, Mohammad Mehdi; Rutt, Brian K.; Kerr, Adam B.
<x xml:space="preserve">Abstract</x> The Bloch–Siegert (B–S) <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2xbk9c2t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> mapping method has been shown to be fast and accurate, yet it suffers from high Specific Absorption Rate (SAR) and moderately long echo time. An adiabatic RF pulse design is introduced here for optimizing the off‐resonant B–S RF pulse to achieve more B–S <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2xbk9c18" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> measurement sensitivity for a given pulse width. The extra sensitivity can be used for higher angle‐to‐noise ratio <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2xbk9c0q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> maps or traded off for faster scans. Using numerical simulations and phantom experiments, it is shown that a numerically optimized 2‐ms adiabatic B‐S pulse is 2.5 times more efficient than a conventional 6‐ms Fermi‐shaped B–S pulse. The adiabatic B–S pulse performance is validated in a phantom, and in vivo brain <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg2xbk9bx3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />B1+</alternatives> mapping at 3T and 7T are shown. Magn Reson Med 70:829–835, 2013. © 2012 Wiley Periodicals, Inc.